Moral justifiability of advance lump sum payment of damages for future medical expenses in medico-legal cases - Thabane, Warrence Mahlomola (My University, 2021)
This report focuses on the moral justifiability of advance lump sum payments for future medical expenses in medico-legal cases. South Africa is experiencing a rapid increase in the number and amount of these claims. If such claims are allowed to continue, this remedial system poses a threat to health services access. I believe the system is neither effective, nor provides restorative justice as intended, because the bulk of the damages claimed end up covering legal costs. An ethico-legal argument is used to demonstrate that: the system is fraught with unethical conduct; it is morally unjustifiable according to Ubuntu; the common law rule that awards in medico-legal cases be made in money is archaic. My conclusion is that these factors show that the practice of advance lump sum payment of future medical expenses is not morally justifiable. A system of mediation where restorative justice and reconciliation is guaranteed is recommended.
A Research Report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Science in Medicine in Bioethics and Health Law.